1993
DOI: 10.1063/1.466058
|View full text |Cite
|
Sign up to set email alerts
|

The solution of the time-dependent Schrödinger equation by the (t,t′) method: Theory, computational algorithm and applications

Abstract: A new powerful computational method is introduced for the solution of the time dependent Schrödinger equation with time-dependent Hamiltonians (not necessarily time-periodic). The method is based on the use of the Floquet-type operator in an extended Hilbert space, which was introduced by H. Sambe [Phys. Rev. A 7, 2203 (1973)] for time periodic Hamiltonians, and was extended by J. Howland [Math Ann. 207, 315 (1974)] for general time dependent Hamiltonians. The new proposed computational algorithm avoids the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
187
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(191 citation statements)
references
References 33 publications
4
187
0
Order By: Relevance
“…It has been shown by Peskin and Moiseyev that by regarding time as an extra coordinate t ′ , one can obtain another Schrödinger equation with a time independent Hamiltonian in the extended Hilbert space (r, t ′ ), whose solution Ψ(r, t ′ , t) has an analytical time dependence (given by the analytical time evolution operator associated with time-independent Hamiltonians) [7]. Our desired wavfunction Ψ(r, t) can be deduced from this wavfunction by a simple operation (that will be shown later).…”
Section: A Brief Review Of the (Tt') Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown by Peskin and Moiseyev that by regarding time as an extra coordinate t ′ , one can obtain another Schrödinger equation with a time independent Hamiltonian in the extended Hilbert space (r, t ′ ), whose solution Ψ(r, t ′ , t) has an analytical time dependence (given by the analytical time evolution operator associated with time-independent Hamiltonians) [7]. Our desired wavfunction Ψ(r, t) can be deduced from this wavfunction by a simple operation (that will be shown later).…”
Section: A Brief Review Of the (Tt') Formalismmentioning
confidence: 99%
“…In order to answer this question we use the (t,t') formalism [7] together with the non-hermitian quantum mechanics (NHQM) formalism. The use of NHQM formalism to describe the dynamics of atoms/molecules subjected to CW laser fields is essential, since only then can the dynamics be described in terms physical, square integrable, resonance Floquet states.…”
Section: Motivationmentioning
confidence: 99%
“…Here we show that these integro-differential equations can be converted to ordinary-differential equations at the expense of introducing a new time variable which is treated as if it is of spatial type. [Similar schemes are employed to numerically solve the Schrödinger equation for time-dependent Hamiltonians [6] and as analytical tools [7]. There is also some resemblence to schemes for solving intego-differential equations of viscoelasticity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Eigenstates of F belong to an extended Hilbert space formed by the composition of the Hilbert space corresponding to the spatial part of the Hamiltonian operator and the space formed by all possible periodic Fourier basis functions of the time coordinate, with finite norm [26]. Yajima [27] and Howland [28] showed that for periodic systems, the so-called Floquet operator, that is, the time-evolution operator during one period T of the external perturbation U (T + t 0 ,t 0 ), and the Floquet Hamiltonian are spectrally equivalent.…”
Section: Appendix A: Rotational Cyclic Statesmentioning
confidence: 99%